The Use of Video Games in Literacy Education and Development: What Have We Learned? - Mahmoodi Shahrebabaki, Masoud (The Journal of Educational Development, 2019)
The growth of video gaming popularity has traversed the entertaining area and is finding its place in the educational arena as well. The educational potentials of video games have prompted literacy practitioners and researchers to embark on using video games for the purpose of increasing the quality and productivity of literacy education. The current theoretical article reviews the latest theories and research findings related to the general use of video games in education with an eye towards the literacy instruction in particular. The material selected for this systematic review consisted of both theoretical and empirical articles about the use of video games in learning and teaching of literacy in the educational contexts. Even though there is tangible evidence as to the positive effects of digital games on students` learning, there is still a dearth of converging evidence as to the practical benefits of inclusion of video games in literacy education. The available evidence are mostly the results of correlational studies, and we still need a connected research stream in pursuit of finding the predictive potentials of the video gaming in literacy instruction.